Formative Assessment in Professional Foreign Language Education: State and Perspectives (Gumilyov Journal of Pedagogy, 2025)
In vocational education, assessment has always been a critical indicator of the knowledge of future specialists. However, in contrast to school assessment procedures, which periodically undergo transformation and are carried out for a wide variety of pedagogical purposes, assessment of higher education over the past 15 years has remained unchanged and, in its own way, traditional. Whereas the content, programme and needs of students may require different approaches to assessment, it is necessary to conduct assessment procedures more often than providing final exams at the end of the semester or academic year. The permanent challenge of the pedagogical process in professional foreign language education is the quality of the education. When the focus is shifted from knowledge-based education to the formation of students’ competency-based skills. Consequently, the content of education was modified, but the system of assessment tools remained the same, not sufficiently capable of assessing other professional indicators of future specialists. Analyzed formative assessment plays a crucial role in higher education by facilitating ongoing feedback between teachers and students, thereby creating a dynamic, personalized learning environment. This article examines the current status of formative assessment in higher foreign language education, discussing teaching strategies and their impact on students learning outcomes in the light of educational experiences, additionally, provides a comparative analysis of formative and traditional assessment systems. Moreover, it identifies gaps in the application of formative assessment in professional foreign language education and predicts prospects for the utilization of this important pedagogical tool that can objectively assess students’ competencies.